(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The utilization of human resources for the socio-economic progress of a nation through industrial and occupational structure, labour force participation has of immense importance. The proportion of workers engaged in various occupations portraits the socio-economic development of a region. Occupation is always associated to agriculture, industry and service sectors. The distribution of workers among different occupational categories along with regional disparities relating to the occupational structure explains the loop-sided development of different parts of India. The study of occupational characteristics and functional classification of towns is of vital importance in understanding their occupational structure and functional association. This study is essential to understand the economic base of towns in the study area. In view of this, the study of occupational structure and functional association of towns has been undertaken.